DEVELOPING A POLICE-COMMUNITY ORGANIZATION PARTNERSHIP FORUM MODEL TO PREVENT POLITICAL CONFLICT IN BANDAR LAMPUNG CITY - Sigit Riyadi; Budi Waskito; Riswan; Malik (International Journal of Multidisciplinary Reseach, 2026)
The main problem in developing the Police and Community Organization Partnership Forum Model in Bandar Lampung City is the absence of a structured and sustainable partnership in preventing political conflict, so that coordination and early detection of conflict have not been running optimally amidst local political dynamics. This study uses a qualitative descriptive method to describe the development of the Police and Community Organization Partnership Forum Model in preventing political conflict in Bandar Lampung City. Data were obtained through interviews and document studies. The results of the study indicate that the partnership forum serves as a forum for communication and cooperation between the National Police and community organizations in maintaining political stability, but its effectiveness is not optimal in terms of communication, participation, member capacity, coordination, and conflict prevention performance. The effectiveness of the forum is determined by interacting structural, institutional, social, and cultural factors, so a more systematic, measurable, and sustainable partnership model is needed.